Increasing recombinant protein production in E. coli via FACS-based selection of N-terminal coding DNA libraries - Herynek, Štěpán; Svoboda, Jakub; Huličiak, Maroš; Peleg, Yoav; Škultétyová, Ľubica; Mikulecký, Pavel; Schneider, Bohdan (The FEBS journal, 2025)
Here, we present a previously undescribed approach to modify N-terminal sequences of recombinant proteins to increase their production yield in Escherichia coli. Prior research has demonstrated that the nucleotides immediately following the start codon can significantly influence protein expression. However, the impact of these sequences is construct-specific and is not universally applicable to all proteins. Most of the previous research has been limited to selecting from a few rationally designed sequences. In contrast, we used a directed evolution-based methodology, screening large numbers of diversified sequences derived from DNA libraries coding for the N-termini of investigated proteins. To facilitate the identification of cells with increased expression of the target construct, we cloned a GFP gene at the C-terminus of the expressed genes and used fluorescent activated cell sorting (FACS) to separate cells based on their fluorescence. By following this systematic workflow, we successfully elevated the yield of soluble recombinant proteins of multiple constructs up to over 30-fold.
Keywords: zelené fluorescenční proteiny; Green Fluorescent Proteins; protein expression optimization; klonování DNA; DNA libraries; directed evolution; rekombinantní proteiny; Recombinant Proteins; N‐terminal sequences; Flow Cytometry; Cloning, Molecular; genová knihovna; Escherichia coli; průtoková cytometrie; Directed Molecular Evolution; fluorescence‐activated cell sorting (FACS); řízená evoluce molekul; Gene Library